Assessing Water Quality of Cisterns in Sha'rawiya Area "Tulkarm Governorate" for Drinking Purposes - Saja Asa'd Almur (My University, 2016)
This study was undertaken to assess the quality of rainwater harvesting (RWH) cisterns for drinking purposes at Sha'rawiya rural area. Fifty water samples were collected from tested cisterns at 12 rural areas. All samples were analyzed for physiochemical parameters (pH, EC, TDS, alkalinity, hardness, turbidity, Ca+2, Mg+2, K+, Na+, Cl-, NO3-, SO4-2, PO4-2, and HCO3-), microbial parameters (TC and FC), and some heavy metals (Ag, Al, Ba, Be, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) using standard procedures. The results were compared with Palestinian standards (PS) and world health organization (WHO) standards of drinking water. Among the analyzed samples, all results of tested physiochemical parameters were within acceptable limits of PS and WHO standards except (4%) of NO3- results, (4%) of turbidity results, (2%) of alkalinity results, (2%) of electric conductivity (EC) results, (2%) of Ca+2 results, and (28%) of Mg+2 results exceeded the PS and WHO standards. The percentage of contamination with TC and FC was 86%, 80%, respectively. All heavy metals were within PS except the iron (Fe) in which (33%) of results exceeded the permissible limits. Cistern characteristics and sources of contamination were studied by the distribution of 100 questionnaires along the study area. The highest percentage of contamination sources: (78%) was detected due to the presence of trees around the cistern, and storage of the first storm of rainwater in the cistern. Almost (36%) of contamination was due to withdrawing water manually. In general, the obtained results of water quality parameters show that some parameters have values higher than standards especially the microbial parameters (TC and FC), this explained the unsuitable use of RWH systems for direct drinking purposes without disinfection processes. This is an indication of contamination hazards and weak drinking water treatment practices in the study area, which in turn have an important effect on human health. Based on total dissolved solids (TDS) as a salinity hazard, the obtained results indicate the possibility to use RWH for irrigation purposes. This study therefore, recommends the responsible authorities to raise public awareness for cistern owners about the best practices to collect and store rainwater, and to take appropriate corrective measures to get high water quality for drinking purposes.

لقد هدفت هذه الدراسة لتقييم جودة المياه في آبار الجمع المنزلية لأغراض الشرب في منطقة الشعراوية والتي تضم 12 منطقة ريفية. حيث تم عمل فحوصات كيميائية وميكروبية لبعض آبار الجمع في منطقة الدراسة، وتم أخذ (50) عينة وأجريت لها بعض الفحوصات المخبرية التي تتضمن درجة الحموضة، الموصلية الكهربائية، البايكربونات، الكلورايد، العسر الكلي، الكالسيوم، المغنيسيوم، النيترايت، الكبريتات، الصوديوم، الفوسفات، العكورة، القاعدية، الحديد، البوتاسيوم، القولونيات الكلية والبرازية، وبعض العناصر الثقيلة. لقد أظهرت النتائج أن معظم العناصر الكيميائية التي تم فحصها ضمن المعايير المسموح بها للشرب محليا وعالميا مع وجود بعض العناصر التي تجاوزت الحد الأقصى المسموح بالنسب التالية النيترايت (4%)، العكورة (4%)، القاعدية (2%)، المغنيسيوم (28%)، الكالسيوم (2%)، و الحديد (33%). وكذلك تم الكشف عن التلوث الميكروبي بالقولونيات الكلية والبرازية التي تجاوزت نسبتها المعايير المسموح بها بمقدار 86%، 80% على الترتيب. لقد تمت دراسة خصائص الآبار ومصادر تلوثها من خلال توزيع (100) استبانة على أصحاب الآبار ومن خلال تحليل الإجابات تم التوصل إلى أن المصدر الرئيسي للتلوث بنسبة (78%) يعزى لوجود أشجار بالقرب من البئر وعدم التخلص من مياه الشتوة الأولى، في حين (36%) من نسبة التلوث تعزى لسحب المياه من البئر يدويا المنزل كمصدر لتجميع مياه المطر. وفي نهاية الدراسة تم التوصل إلى عدم إمكانية استخدام مياه الجمع لأغراض الشرب بشكل مباشر وبدون معالجة نظرا لارتفاع نسبة الملوثات الميكروبية، في حين يمكن استخدامها لأغراض الري
تقييم جودة مياه آبار الجمع لأغراض الشرب في منطقة الشعراوية " محافظة طولكرم